Chemical composition and evaluation of antioxidant, antimicrobial and antiproliferative activities of Tuber and Terfezia truffles. (February 2021) - Tejedor-Calvo, Eva; Amara, Khira; Reis, Filipa S.; Barros, Lillian; Martins, Anabela; Calhelha, Ricardo C.; Venturini, Maria Eugenia; Blanco, Domingo; Redondo, Diego; Marco, Pedro; Ferreira, Isabel C.F.R.
Graphical abstract: Highlights: Truffles are a rich source of carbohydrates and proteins. Oleic, linoleic and palmitic acids were the main truffle fatty acids. Oxalic and fumaric acids and tocopherols (α, β, γ and δ) were found in truffles. T. magnatum contained the highest TPC values and the highest antioxidant activity. Terfezia and T. gennadii extracts revealed antiproliferative activity. Abstract: Ten truffle species of Tuber and Terfezia genera were chemical characterized, assessing their proximate composition, individual nutrient compounds and some bioactive molecules. The bioactive properties of these species were also evaluated, namely their antioxidant, antimicrobial and cytotoxic potential. Carbohydrates were the main macronutrients present in truffles, followed by proteins. Furthermore, the levels of polyunsaturated fatty acids (PUFA), subsequently presented as a percentage, were higher in truffles (38.2–79.3%) except in Tuber magnatum and Terfezia arenaria, which have a more saturated fatty acids (SFA) profile (70.7% and 53.7%, respectively). Comparing the species, T. magnatum revealed the highest levels of total phenolic compounds (TPC) (290 mg GAE/100 g truffle), as also the best results in the four methods used to evaluate the antioxidant activity. On the other hand, only five extracts obtained from some studied truffle species ( Terfezia magnusii, Tuber aestivum, Tuber gennadii, and Tuber melanosporum ) showed a slight inhibition of microbial growth, tested against different bacteria. Terfezia and T. gennadii extracts, showed potential to inhibit the cellular growth of NCI-H460, HeLa, HepG2, and MCF-7 cell lines (GI50 concentrations range: 19–78, 33–301, 83–321 and 102–321 µg/mL, respectively), indicating anti-proliferative activity. Nevertheless, T. arenaria revealed some potential hepatotoxicity, inhibiting the growth of PLP2 cells (GI50 concentration of 220 µg/mL), a primary cell culture obtained from porcine liver.